ANALISIS YURIDIS TERHADAP PUTUSAN ARBITRASE INTERNASIONAL YANG DIBATALKAN OLEH PENGADILAN NEGERI JAKARTA PUSAT (Studi Putusan Nomor: 631 K/ Pdt. Sus/ 2012) - RACHEL YOVANI ADRIANI NAPITUPULU (Ilmu Hukum Prima (IHP), 2021)
Arbitration is dispute settlement outside the court which is final and binding. In an international contract, if the parties prefer to settle disputes through arbitration, arbitration institution has absolute authority to settle them. However, the implementation of arbitral decision is not effective yet, because the parties in some cases are found to be not ready to accept and respect an arbitral decision, so they submit a lawsuit to a District Court. This can be seen in the dispute between Harvey Nichols and Company Limited against Hamparan Nusantara Company and Mitra Adiperkasa Company. This is a normative juridical research with descriptive analysis. The main data consist of secondary data collected from library study and processed from primary, secondary, and tertiary legal materials. Data collection instruments used is document study, then the data obtained are analyzed qualitatively. The results demonstrate that the legal implications of the preference of law and forum approved by Harvey Nichols and Company Limited with Hamparan Nusantara Company and Mitra Adiperkasa Company is the enactment of the Substantive Law of England and Wales and the dispute settlement forum used is an arbitration forum based in London, England. Analysis of judge’s legal considerations in this case is that the South Jakarta District Court is not supposed to be authorized to verify lawsuit in this case. In addition, it is necessary to have good faith of the parties to respect the arbitration clause in the contract, so that the arbitration clause can be effective. Reconstruction of the revocation of the arbitration decision is also required because there is still a disharmony between the laws on judge’s authority in Indonesia and the laws on arbitration that there is a legal gap that can be used by parties who are not satisfied with the arbitration decision. It is suggested that business actors be aware before binding themselves in a contract because the preference of law and forum clauses be carried out according to the agreement in case of any dispute in the future. Supervision from the Supreme Court and the Judicial Commission is also necessary, so that the judges do not give decisions that deviate from positive law in Indonesia. Then, a revision of the Arbitration Law is also needed to create arbitration independence as a dispute settlement forum in Indonesia.